Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. HAHA Spektrum Indonesia - Siti Nur Halizah; Taat Kuspriyono (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Human Resources plays a very important role in the company and can be used to run other workforce to achieve company goals. This research is to determine the influence of Motivation and Work Environment on Employee Performance at PT. HAHA Indonesian Spectrum. In this research, the research design used by the author uses quantitative methods. The sampling technique in this research used a saturated sampling technique. Data collection on respondents' answers in this research questionnaire used a Likert scale. The number of samples used was 41 employees at PT. HAHA Spektrum Indonesia and tested using SPSS Version 25. In the calculation results of the hypothesis test, an F value of 32.433 > 3.24 F Table was obtained and was supported by a significant value of 0.000, where the conditions accepted in this hypothesis were a significant value of less than 0, 05 and obtained a t value of 2.262 > t table 2.024 with a significant value of 0.029, where the significant value is less than 0.05. So from the test results in the problem formulation in this research, it is stated whether there is an influence on Motivation and Work Environment on Employee Performance at PT. HAHA Indonesian Spectrum, namely the existence of influence and Hypothesis H3 is accepted.